2023
DOI: 10.1037/lat0000217
|View full text |Cite
|
Sign up to set email alerts
|

“Así es la vida”: Stress, control, and coping among Latino/a immigrants.

Abstract: Scholars are increasingly researching the influence of sociocultural factors on the stress-coping process. However, research on the stress-coping process among Latinx immigrants remains understudied despite significant population growth in the United States. This qualitative study sought to better understand how Latinx immigrants experience stress and how they cope with it. Drawing from focus groups with 23 Latino/a immigrant participants living in and around Charlotte, North Carolina, we present how they conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We also examined whether documentation and health insurance statuses, level of trust and place of birth predicts the severity of the pandemic's effects. This project uses Community-Based Participatory Research (CBPR) approaches, which are effective in conducting research and improving health outcomes in Latino immigrants (Caro et al, 2023(Caro et al, , 2021Salimi et al, 2012). The project was conducted in direct response to local community needs, and Latino community members participated in survey development, recruitment and dissemination of findings.…”
Section: Methodsmentioning
confidence: 99%
“…We also examined whether documentation and health insurance statuses, level of trust and place of birth predicts the severity of the pandemic's effects. This project uses Community-Based Participatory Research (CBPR) approaches, which are effective in conducting research and improving health outcomes in Latino immigrants (Caro et al, 2023(Caro et al, , 2021Salimi et al, 2012). The project was conducted in direct response to local community needs, and Latino community members participated in survey development, recruitment and dissemination of findings.…”
Section: Methodsmentioning
confidence: 99%
“…By the Year 2050, it is estimated that Latinxs will represent 30% of the total U.S. population. While increases in the Latinx population have slowed in traditional resettlement locations, the rate of growth in southeastern U.S. states has increased exponentially (Caro et al, 2023; Powell & Carrillo, 2019; Topmiller et al, 2017). These rapid increases have created challenges for nontraditional receiving communities.…”
Section: Well-being and The Convoy Model Of Social Relationshipsmentioning
confidence: 99%
“…The Latinx population has been the largest ethnic group in the United States over the last 20 years (Garcia & Lindgren, 2009). In 2015, young adults represented one-fourth of this population (Patten, 2016), with one and five of all millennials in southeastern U.S. states has increased exponentially (Caro et al, 2023;Powell & Carrillo, 2019;Topmiller et al, 2017). These rapid increases have created challenges for nontraditional receiving communities.…”
mentioning
confidence: 99%
“…Many studies have found that Latinx individuals commonly rely on their faith and spirituality to cope with stress (e.g., Koerner et al, 2013; Moreno et al, 2017; Silva et al, 2017). Specifically, they engage in strategies such as prayer, seeking social support in their religious communities, reading scripture, and attending church (e.g., Caro et al, 2023). However, the vast majority of studies that have examined religious coping with Latinx samples have done so with adults.…”
Section: Important Considerations and Next Stepsmentioning
confidence: 99%